1994
DOI: 10.1002/sia.740210807
|View full text |Cite
|
Sign up to set email alerts
|

XPS and static SIMS studies of copoly(ether–esters) containing mixed polyether soft blocks

Abstract: The surface compositions for a series of copoly(ether-esters) are determined from XPS and static SIMS measurements. The copolymers consist of a polybutylene terephthalate (PBT) hard block and a mixed soft block of two of the following polyethers-poly(propy1ene glycol) (PPG), poly(tetramethy1ene oxide (PTMO) and poly(ethy1ene oxide) (PEO). The surfaces of all the copolymers are enriched in the total polyether soft blocks. Quantification of XPS intensities shows the presence of both polyethers at the surface of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Also complicated copolymer systems are amenable. Burrell et al (1994) investigated multiblock poly(ester-bether)s with poly(butylene terephtalate and poly(hexamethylene terephtalate) hard segments and a mixture of PEG, PPG and tetramethylene oxide as soft segments. In more complex samples, S-SIMS provides a distinct advantage over XPS since the latter method requires that all the components of the system and their spectra are known in advance.…”
Section: Methodology and Structural Interpretationmentioning
confidence: 99%
“…Also complicated copolymer systems are amenable. Burrell et al (1994) investigated multiblock poly(ester-bether)s with poly(butylene terephtalate and poly(hexamethylene terephtalate) hard segments and a mixture of PEG, PPG and tetramethylene oxide as soft segments. In more complex samples, S-SIMS provides a distinct advantage over XPS since the latter method requires that all the components of the system and their spectra are known in advance.…”
Section: Methodology and Structural Interpretationmentioning
confidence: 99%
“…He suggested that the differences in the surface free energy of various components within a polymer membrane may dominate the overall surface morphology, whereby the lower surface energy segment resided near the polymer-air interface [16,17,[48][49][50].…”
Section: Surface Behavior Of Copolymer Speek-hq Membranementioning
confidence: 99%
“…In some polymer systems, the composition of the membrane surface differs, sometimes dramatically, from the composition within the bulk, resulting in a material with distinct surface properties, such as wettability and adhesion. Differences of the surface free energy of the components within a polymer may explain the overall surface morphology in which the lower surface energy component of polymer preferentially aggregates towards the polymer-air interface [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…PBT-based TPEE has been developed, such as poly(butylene terephthalate- co -polyethylene glycol) (PBT- co -PEG) [ 16 , 31 ] and poly(butylene terephthalate- co -polypropylene glycol) (PBT- co -PPG) [ 32 ], revealing varied characteristics depending on different compositions. Poly(butylene terephthalate- co -tetramethylene ether glycol) (PBT- co -PTMEG) copolymer was first commercialized under the trademark “Hytrel” (Du pont, Wilmington, DE, United States) as engineering plastics in 1972 [ 33 , 34 , 35 ], and the morphology [ 17 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ], properties [ 45 , 46 , 47 , 48 , 49 ], interactions between hard segments and soft segments [ 50 , 51 ], and structure of the crystalline [ 36 , 38 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ] and amorphous phase [ 5 , 17 , 49 , 59 ] have been studied extensively. The crystalline regions of PBT- co -PTMEG copolymers are continuous and highly interconnected, dispersing in a continuous amorphous region [ 52 , 60 ].…”
Section: Introductionmentioning
confidence: 99%